Assessment of anti-CD20 antibody pre-treatment for augmentation of CAR-T cell therapy in SIV-infected rhesus macaques - Pampusch, Mary S.; Sevcik, Emily N.; Quinn, Zoe E.; Davey, Brianna C.; Berg, James M.; Gorrell-Brown, Ian; Abdelaal, Hadia M.; Rakasz, Eva G.; Rendahl, Aaron; Skinner, Pamela J. (Frontiers in Immunology, 2023)
During chronic HIV and SIV infections, the majority of viral replication occurs within lymphoid follicles. In a pilot study, infusion of SIV-specific CD4-MBL-CAR-T cells expressing the follicular homing receptor, CXCR5, led to follicular localization of the cells and a reduction in SIV viral loads in rhesus macaques. However, the CAR-T cells failed to persist. We hypothesized that temporary disruption of follicles would create space for CAR-T cell engraftment and lead to increased abundance and persistence of CAR-T cells. In this study we treated SIV-infected rhesus macaques with CAR-T cells and preconditioned one set with anti-CD20 antibody to disrupt the follicles. We evaluated CAR-T cell abundance and persistence in four groups of SIVmac239-infected and ART-suppressed animals: untreated, CAR-T cell treated, CD20 depleted, and CD20 depleted/CAR-T cell treated. In the depletion study, anti-CD20 was infused one week prior to CAR-T infusion and cessation of ART. Anti-CD20 antibody treatment led to temporary depletion of CD20+ cells in blood and partial depletion in lymph nodes. In this dose escalation study, there was no impact of CAR-T cell infusion on SIV viral load. However, in both the depleted and non-depleted animals, CAR-T cells accumulated in and around lymphoid follicles and were Ki67+. CAR-T cells increased in number in follicles from 2 to 6 days post-treatment, with a median 15.2-fold increase in follicular CAR-T cell numbers in depleted/CAR-T treated animals compared to an 8.1-fold increase in non-depleted CAR-T treated animals. The increase in CAR T cells in depleted animals was associated with a prolonged elevation of serum IL-6 levels and a rapid loss of detectable CAR-T cells. Taken together, these data suggest that CAR-T cells likely expanded to a greater extent in depleted/CAR-T cell treated animals. Further studies are needed to elucidate mechanisms mediating the rapid loss of CAR-T cells and to evaluate strategies to improve engraftment and persistence of HIV-specific CAR-T cells. The potential for an inflammatory cytokine response appears to be enhanced with anti-CD20 antibody treatment and future studies may require CRS control strategies. These studies provide important insights into cellular immunotherapy and suggest future studies for improved outcomes.